2003
DOI: 10.1152/ajplung.00434.2002
|View full text |Cite
|
Sign up to set email alerts
|

Induction of arginase I and II in bleomycin-induced fibrosis of mouse lung

Abstract: Arginase, which hydrolyzes arginine to urea and ornithine, is a precursor for the synthesis of polyamines and proline, which is abundant in collagen. The supply of proline can be a crucial factor in the process of lung fibrosis. We investigated the induction of arginine metabolic enzymes in bleomycin-induced mouse lung fibrosis. Histological studies and quantification of lung hydroxyproline showed that lung fibrosis develops in up to 14 days after bleomycin treatment. Under these conditions, collagen I mRNA wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
87
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 50 publications
6
87
0
Order By: Relevance
“…In support of this, the profibrotic factor TGF-b has been shown to induce arginase activity in mouse lung and fibroblasts [45]. Moreover, increased expression of arginases I and II was closely associated with increased collagen I and hydroxyproline expression in bleomycin-induced lung fibrosis in mice [27,46]. Using inhaled ABH, we now demonstrate that increased arginase activity contributes to allergen-induced fibrosis as well.…”
Section: Discussionsupporting
confidence: 55%
“…In support of this, the profibrotic factor TGF-b has been shown to induce arginase activity in mouse lung and fibroblasts [45]. Moreover, increased expression of arginases I and II was closely associated with increased collagen I and hydroxyproline expression in bleomycin-induced lung fibrosis in mice [27,46]. Using inhaled ABH, we now demonstrate that increased arginase activity contributes to allergen-induced fibrosis as well.…”
Section: Discussionsupporting
confidence: 55%
“…Arginase II also plays a role in collagen synthesis as was shown in a murine model of bleomycin-induced fibrosis. 33 In addition, Que and colleagues 34 showed the induction of arginase I and II during the fibroproliferative phase of hyperoxic lung injury in rats. The increase in arginase II in our model when peribronchiolar fibrosis (40 days) is observed is consistent with its involvement in repair processes.…”
Section: Discussionmentioning
confidence: 99%
“…As a modulator of NO-dependent macrophage cytotoxicity, arginase I is implicated in the regulation of macrophage activity in wound healing (8) and the suppression of the tumoricidal activity of macrophages (9) and T cells (10). Notably, arginase I is very highly up-regulated in the murine spinal cord during experimental autoimmune encephalomyelitis, an animal model for human multiple sclerosis (11), and it is up-regulated in the inflammatory regions of the asthmatic lung (12)(13)(14).Arginase I in the immune response is also implicated in cancer biology: arginase I is significantly up-regulated and promotes tumor cell growth in breast cancer (15, 16) and colorectal cancer (17). Rodriguez et al (10, 18, 19) recently demonstrated that macrophages stimulated by interleukins 4 and 13 produce high levels of arginase I and cause T-cell anergy by decreasing the expression of the T-cell receptor CD3 chain; furthermore, arginase inhibition blocks the growth of lung carcinoma in a murine model.…”
mentioning
confidence: 99%
“…As a modulator of NO-dependent macrophage cytotoxicity, arginase I is implicated in the regulation of macrophage activity in wound healing (8) and the suppression of the tumoricidal activity of macrophages (9) and T cells (10). Notably, arginase I is very highly up-regulated in the murine spinal cord during experimental autoimmune encephalomyelitis, an animal model for human multiple sclerosis (11), and it is up-regulated in the inflammatory regions of the asthmatic lung (12)(13)(14).…”
mentioning
confidence: 99%